Comparison of treadmill and kayak ergometer protocols for evaluating peak oxygen consumption - Rodrigues dos Santos, J. A.; Santos Sousa, R. F.; Amorim, T. P. (The Open Sports Sciences Journal, 2012)
The main goal for training in sport is to elicit the adequate physical loads to induce the desired adaptations. To achieve this goal it is necessary to continuously assess the alterations induced by training, which can be done by field or laboratory tests. The aim of the present study is to compare peak oxygen consumption of elite kayakers on treadmill and kayak ergometer protocols in two moments of a training season. Five elite sprint kayakers performed two maximal tests (treadmill and kayak ergometer) to assess peak oxygen consumption, maximum heart rate, and performance indicators. Tests were conducted in two different moments of the season: in the preparatory period in October (M1), and in the competitive period in April (M2). Peak oxygen consumption on treadmill were 4.66±0.44 L.min-1 (58.4±3.3 ml.kg-1.min-1) and 4.55±0.31 L.min-1 (58.0±3.2 ml.kg-1.min-1) in M1 and M2, respectively; on kayak ergometer the values for this parameter were 4.47±0.40 L.min-1 (56.04±4.18 ml.kg-1.min-1) and 4.17±0.60 L.min-1 (53.21±8.36 ml.kg-1.min-1) in M1 and M2, respectively. The statistical analyses (Friedman Test and Test T Wilcoxon) showed no significant differences (p>0.05) between ergometers in the two moments of the study. The data obtained, both in treadmill and kayak ergometer, also showed no significant differences (p>0.05) between moments of a training season. It was concluded that in well trained kayakers the achievement of peak oxygen consumption is similar using treadmill or kayak ergometer exercise, and that this parameter is not suitable to detect performance alterations during the season.